2013
DOI: 10.1002/isaf.1335
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Feature Selection: A Data‐mining Application in Direct Marketing

Abstract: SUMMARY The capability of identifying customers who are more likely to respond to a product is an important issue in direct marketing. This paper investigates the impact of feature selection on predictive models which predict reordering demand of small and medium‐sized enterprise customers in a large online job‐advertising company. Three well‐known feature subset selection techniques in data mining, namely correlation‐based feature selection (CFS), subset consistency (SC) and symmetrical uncertainty (SU), are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In other words, DM has the potential to transform traditional SMEs to organizations with a competitive advantage. For instance, suppose an SME aims to mine its customer data, the potential benefit would entail creating cross-selling avenues at a higher margin, improving its customer retention and satisfaction rates, identifying the most profitable customer group and last but not least, enhancing the SME's marketing and sales strategy (Tan, Yeoh, Boo, & Liew, 2013). In the mining of inventory data, on the other hand, SMEs can gain an advantage by forecasting the inventory that will help reduce the total value of stock held.…”
Section: What Dm Can Mean For Smes?mentioning
confidence: 99%
“…In other words, DM has the potential to transform traditional SMEs to organizations with a competitive advantage. For instance, suppose an SME aims to mine its customer data, the potential benefit would entail creating cross-selling avenues at a higher margin, improving its customer retention and satisfaction rates, identifying the most profitable customer group and last but not least, enhancing the SME's marketing and sales strategy (Tan, Yeoh, Boo, & Liew, 2013). In the mining of inventory data, on the other hand, SMEs can gain an advantage by forecasting the inventory that will help reduce the total value of stock held.…”
Section: What Dm Can Mean For Smes?mentioning
confidence: 99%
“…Thus, several studies were published related to the application of feature selection to CT [17]. A recent study authored by Tan et al [18] shows the impact of feature selection in direct marketing. Their work analysed three filter methods for feature selection (correlation-based feature selection, subset consistency and symmetrical uncertainty), concluding that symmetrical uncertainty resulted in better models, outperforming both the two remaining methods studied and a model without any feature selection procedure.…”
Section: Introductionmentioning
confidence: 99%
“…While there are several studies published on feature selection using MI, and a few using SA, none performed a direct comparison on both methods to assess the pros and cons on using each. Furthermore, even though a handful of recent studies were found comparing feature selection methods through practical applications [18], none considered SA. The main contributions of this study are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Through an extensive conducted it was uncovered that the hindrance factors of data analytics adoption are in the area of data management, knowledge management and data management [9]. Data Mining (DM) is cru-cial for SMEs, especially so, in the private transport domain as the organisation can inherently extract and process its dataset to uncover new insights to facilitate better decision for the business [10,11]. In an extensive study of DM application by the large transportation enterprise and SMEs context at large, it was uncovered that the CRISP-DM methodology is the most popular applied DM model by the industry [9].…”
Section: Introductionmentioning
confidence: 99%